THE ISSUE OF VALUES IN THE SYSTEM OF CULTURE (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article analyzes the issue of values within the system of culture from a scientific and theoretical perspective. It examines the essence of the concept of values, their role in social life, their functions within the cultural system, and the transformation of values in the context of globalization. The article also explores the relationship and harmony between national and universal values.